Исследование масляных экстрактов древесной зелени хвойных пород методом газовой хроматографии - Мудрикова, Алена Евгеньевна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
In this work, the chromatographic conditions for the separation of key and minor components of coniferous greenery oil extracts were developed. A method for the quantitative determination of key components in oil extracts was developed and their quantitative content in the presented samples was determined. The quantitative distribution of the target components (borneol, bornyl acetate) by fractions was investigated.